Pengaruh Penempatan Kerja, Lingkungan Kerja dan Kerjasama Tim Terhadap Kinerja Karyawan pada UD. Brontoseno Nganjuk - Cinthia Putri Anggraeni; Moch. Saleh Udin; Trisnia Widuri (Nian Tana Sikka : Jurnal ilmiah Mahasiswa, 2023)
This research aims to determine the influence of work placement variables (X1), work environment (X2), and teamwork (X3) on employee performance (Y) at UD Brontoseno Nganjuk. This type of research is quantitative research. The data collection techniques used are primary data and secondary data. The sample selection used the saturated sampling method, the number of samples in the study was 33 respondents at UD Brontoseno Nganjuk. The analysis techniques used are Validity Test, Reliability Test, Classical Assumption Test, Multiple Linear Regression Analysis, T Test, F Test and Coefficient of Determination Test. The results of the research obtained the multiple linear regression equation Y= -10.801 + 0.911X1 + 1.196X2 + 0.465X3 and the results of the t test for the variables of work placement, work environment and teamwork had a partially significant effect on employee performance with sig < 0.05. The F test results obtained Fcount results with a significance value of 0.000 < 0.05. From the results of the analysis it can be concluded that work placement, work environment and teamwork simultaneously have a significant effect on the performance of UD Brontoseno Nganjuk employees.